Attitude of Third-Year Internships in Thailand: To be or not to be in Obstetrics and Gynecology Residency Training ? - Yuphadee Tokhao; Apichart Chittachareon (The Royal Thai College of Obstetricians and Gynaecologists, 2009)
Objective: To determine the opinion to pursue the residency training in Obstetrics and Gynecology of third-year internships who work in Thailand. Materials and methods: This is a cross-sectional descriptive study. Questionnaires consisted of demographic question, questions about desire and factors influencing their selection for residency training in Obstetrics and Gynecology and other fields were sent to all third-year internships in Thailand. Results: Eight hundred and seventy six third-year internships (57.8% of all third-year internships) completed the questionnaires. Only 69 respondents (8.4%) chose Obstetrics and Gynecology residency training. Positive factors influencing their decisions included the chance of practicing surgical procedure, the inhancing the ability of taking care pregnant women and child birth and good impression of the instructors. On the contrary, negative factors included high risk of litigation and serious complications, unusual life-style of obstetrician had poor impact on the internship selection of specialty. Conclusions: Only 8.4% of third-year internships decided to pursue residency training in Obstetrics and Gynecology. The risk of law suits and life-style issues might detract them from pursuing Obstetrics and Gynecology residency training.